Metamaterials for Subwavelength Imaging - Kiran Kumar Amireddy; S. Solomon Raj (Techniques and Innovation in Engineering Research Vol. 5, 2023)
Metamaterials (MM) with their exotic properties that are not observed in naturally existing materials are of much interest in many fields including medical diagnostics and non-invasive imaging and testing of industrial components. Advances such as super and hyper lenses, extraordinary transmission, cloaking and absorption, have been experimentally demonstrated with metamaterials. These can be treated as effective media, where their extraordinary properties depend on the periodic geometrical and topographic features. This chapter explains the Optical (Electromagnetic) and the Acoustic Metamaterials used for subwavelength imaging.